Evaluation of Bispectral Index time delay in response to anesthesia induction: an observational study - Ferreira,Ana Leitão (2019)
Abstract Background and objectives According to the manufacturer, the Bispectral Index (BIS) has a processing time delay of 5-10 s. Studies addressing this have suggested longer delays. We evaluated the time delay in the Bispectral Index response. Methods Based on clinical data from 45 patients, using the difference between the predicted and the real BIS, calculated during a fixed 3 minutes period after the moment the Bispectral Index dropped below 80 during the induction of general anesthesia with propofol and remifentanil. Results The difference between the predicted and the real BIS was in average 30.09 ± 18.73 s. Conclusion Our results may be another indication that the delay in BIS processing may be much longer than stated by the manufacture, a fact with clinical implications.